Redesigning work how to transform your organization and make hybrid work for everyone - Gratton, Lynda (Cambridge The Mit Press, 2022)
How companies can use the recent shifts in business norms and culture to reset work for the coming decade and beyond
Includes index
Keywords: Personnel management